Wortmannin inhibits the effects of insulin and serum on the activities of glycogen synthase kinase-3 and mitogen-activated protein kinase. - Welsh, G I (1994)
We have previously shown that insulin causes inactivation of glycogen synthase kinase-3 (GSK-3) in Chinese hamster ovary cells over-expressing the human insulin receptor (CHO.T cells). We now show that serum and phorbol ester also cause rapid inactivation of GSK-3, both in CHO.T cells and in the nontransfected parental cell line, CHO.K1 cells. Rapamycin was without effect on the inactivation of GSK-3 by insulin, serum or phorbol ester, indicating that the p70 S6 kinase pathway is not involved. In contrast, wortmannin, a potent inhibitor of phosphatidylinositol 3-kinase, blocked the effects of both insulin and serum on GSK-3 activity, and also substantially reduced the activation of both p90 S6 kinase (by insulin) and mitogen-activated protein (MAP) kinase (by insulin and serum). These findings imply (i) that GSK-3 activity is regulated by a cascade involving MAP kinase and p90 S6 kinase and (ii) that wortmannin affects an early step in the MAP kinase pathway. One can infer from this that GSK-3 may be an important regulatory enzyme for the control of several biosynthetic pathways, key enzymes in which are regulated by GSK-3-mediated phosphorylation. Wortmannin had a smaller effect on the activation of MAP kinase by phorbol ester, indicating that phorbol esters may stimulate MAP kinase by a different or additional mechanism to that employed by insulin or serum. Wortmannin had very little effect on the inactivation of GSK-3 by phorbol ester: possible reasons for this are discussed.